First Permanent Molar Caries and Oral Health Practices in Saudi Male Teenagers: Inequalities by Socioeconomic Position. (17th August 2020) - Bakhurji, Eman; Gaffar, Balgis; Nazir, Muhammad; Al-Khalifa, Khalifa; Al-Ansari, Asim
Abstract : Objectives . Caries remains a problem in high-risk groups aggravated by socioeconomic inequalities. The study aimed to investigate (1) oral health practices associated with caries in the 1 st permanent molars in Saudi male teenagers and (2) the impact of socioeconomic position (SEP) on caries control using these practices. Methods . A cross-sectional study targeted 1137 male teenagers in intermediate schools in Khobar and Dammam, Saudi Arabia, in 2016. Caries was examined using the World Health Organization criteria and plaque was assessed using the plaque index of Loe and Silness. A questionnaire assessed SEP (parental education, employment, and home ownership) and oral health practices (using fluoridated toothpaste twice daily, regular dental visits for check-ups, and avoiding daily sugary snacks). Regression models analysed the association of these factors with caries presence and the mean number of decayed 1 st permanent molars. Stratification was used to assess differences between SEP levels. Results . The response rate was 81.7%. Caries prevalence and mean (SD) number of decayed 1 st permanent molars were 50.4% and 1.08 (1.31). The use of fluoride toothpaste was associated with lower odds of caries and fewer decayed molars (OR = 0.50 and regression coefficient = −0.35). Differences in the relationship between caries and toothpaste were observed by SEP levels with stronger associations in less advantaged groups. Conclusions . Brushing twice daily using fluoride toothpaste was associated with less caries in Saudi male teenagers with stronger association observed in groups with lower SEP. The use of fluoride toothpaste helps in reducing health inequalities associated with SEP.